2005
DOI: 10.1002/elps.200500173
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic flow focusing: Drop size and scaling in pressureversus flow-rate-driven pumping

Abstract: We experimentally study the production of micrometer-sized droplets using microfluidic technology and a flow-focusing geometry. Two distinct methods of flow control are compared: (i) control of the flow rates of the two phases and (ii) control of the inlet pressures of the two phases. In each type of experiment, the drop size l, velocity U and production frequency f are measured and compared as either functions of the flow-rate ratio or the inlet pressure ratio. The minimum drop size in each experiment is on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
256
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(273 citation statements)
references
References 20 publications
15
256
0
2
Order By: Relevance
“…Since the generation of droplets with a predictable and reproducible size and size distribution determines their potential applications (including the synthesis of polymer colloids), several research groups have explored various aspects of the process of emulsification (Seo et al 2005a;Xu et al 2005;Zhang et al 2006;Cygan et al 2005;El-Ali et al 2005;Garstecki et al 2005a;Hudson et al 2005;Jensen and Lee 2004;Khan et al 2004;Song et al 2003;Zheng and Ismagilov 2005;Zheng et al 2003) . It has been observed that the size of droplets is controlled by the design of the microfluidic device (Sugiura et al 2002a, b;Tan et al 2006), the properties of liquids, and the rates of flow of two immiscible phases (Cramer et al 2004;GananCalvo 1998;Ganan-Calvo and Gordillo 2001;Garstecki et al 2004Garstecki et al , 2005aGarstecki et al , 2005bGarstecki et al , 2006Thorsen et al 2001;Serra et al 2007;Tice et al 2003;Ward et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since the generation of droplets with a predictable and reproducible size and size distribution determines their potential applications (including the synthesis of polymer colloids), several research groups have explored various aspects of the process of emulsification (Seo et al 2005a;Xu et al 2005;Zhang et al 2006;Cygan et al 2005;El-Ali et al 2005;Garstecki et al 2005a;Hudson et al 2005;Jensen and Lee 2004;Khan et al 2004;Song et al 2003;Zheng and Ismagilov 2005;Zheng et al 2003) . It has been observed that the size of droplets is controlled by the design of the microfluidic device (Sugiura et al 2002a, b;Tan et al 2006), the properties of liquids, and the rates of flow of two immiscible phases (Cramer et al 2004;GananCalvo 1998;Ganan-Calvo and Gordillo 2001;Garstecki et al 2004Garstecki et al , 2005aGarstecki et al , 2005bGarstecki et al , 2006Thorsen et al 2001;Serra et al 2007;Tice et al 2003;Ward et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…4 Junctions of such flow-focusing devices typically consist of a pair of inlets intersecting the main channel at an angle of 90° or less. [5][6][7] These devices operate at flow rates with a very low Capillary number, 15 , which describes the competition between viscous forces and interfacial tension forces; here is the viscosity of the outer phase, its flow rate, its cross-sectional area, and γ the interfacial tension. In this case, drops form in the squeezing regime where the 20 inner phase penetrates into the junction and blocks it almost entirely, thereby preventing the outer phase from entering the main channel before the inner phase starts to neck.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, drops form in the squeezing regime where the 20 inner phase penetrates into the junction and blocks it almost entirely, thereby preventing the outer phase from entering the main channel before the inner phase starts to neck. In this regime, the dynamics of drop breakup is entirely controlled by the flow rate of the 25 outer phase, 8 such that the drop size depends on the flow rate of the outer phase, 6, 9 its viscosity and surface tension, 10 and the channel geometry. 7,11,12 However, the necking process, which eventually leads to drop formation, is slow, limiting the maximum drop 30 generation frequency and hence the throughput.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of microfluidics is the generation of low volume reactions and high throughput tests, allowing for multiplexing that gives the opportunity to test many antibiotics against any bacterial sample. Microfluidic droplets have been established as chemical bioreactors 8 and have been proven in miniaturizing many biological processes such as PCR, 9 protein crystallization 10 and bio-sensing. 11 Bacterial analysis using microfluidic systems have been established however, the requirement of tools such as a high powered microscope 7 and fluorescence 7,8,12,13 make these systems less viable alternatives.…”
Section: Introductionmentioning
confidence: 99%